Contract Form, Wage Flexibility, and Employment - Lemieux, Thomas; MacLeod, W. Bentley; Parent, Daniel (American Economic Review, 2012)
We begin with two uncontroversial hypotheses - firm productivity is expensive to measure and employment entails relationship-specific investments. These assumptions imply that firms would optimally choose fixed-wage contracts, and complement these with bonus pay when measuring employee performance is not too costly. These assumptions imply that under an optimal employment contract hours of work is less responsive, while total compensation is more responsive to shocks under bonus-pay contracts compared to fixed wage contracts. Using data from the Panel Study of Income Dynamics (PSID) where shocks are proxied using the local unemployment rate, we find strong support for these two implications.